Graded refractive index metamaterial for enhanced far-field wireless power transfer efficiency in S-band - Kulkarni, Shashank S.; Baghel, Amit Kumar; Nayak, Sisir Kumar (International journal of electronics and communications, 2021)
A graded refractive index metamaterial (MM) exhibits a magnetic dipole designed and demonstrated experimentally for 2.45 GHz operating frequency. The system efficiency of the far-field wireless power transfer technique increased to 32.6% with MM. With 16° reduction in half power beamwidths, 9.78 dBm is received at 1 m with 30 dBm input when MM is placed at an optimum distance of 2.5λ0 from transmitting antenna aperture. The method is studied experimentally, and results are compared with the Friis transmission equation, thus validating experimental and theoretical analysis. The system efficiency is always higher than the system with no MM, and hence the proposed method is suitable for long-range wireless power transfer applications maximizing the theoretical power received.